Enhanced piezo‐electric property induced in graphene oxide/polyvinylidene fluoride composite flexible thin films. Issue 11 (31st July 2017) - Bhunia, Ritamay; Dey, Rajkumar; Das, Shirsendu; Hussain, Shamima; Bhar, Radhaballav; Kumar Pal, Arun
Abstract : Graphene oxide/PVDF composite free‐standing flexible films were prepared with different amount of GO fillers in PVDF matrix using sol‐gel technique. The films were characterized by Field emission scanning electron microscopy, X‐ray diffraction, Fourier transform infrared spectroscopy (FTIR), X‐ray photoelectron spectroscopy (XPS) and Raman studies. Results FTIR, XPS, and Raman were critically analysed for modulation of bonding ambience. The GO/PVDF composite films indicated films to be sp 2 rich. Departure from centro‐symmetry of GO when embedded in PVDF matrix leading towards efficient nanogenerator application is discussed critically in the light of Raman and XPS studies. High output voltage was recorded for the unpoled film while the poled samples indicated very negligible output. A rectifying circuit was used to charge a capacitor which was discharged for supplying energy to trigger a red light emitting diode. A maximum a.c. output voltage of ±28V was recorded at microwatt power level. Increments in output voltages with increased GO loading in the PVDF matrix were observed. POLYM. COMPOS., 39:4205–4216, 2018. © 2017 Society of Plastics Engineers